(untitled) (jornal of the libyan geographical society, 1997)
This paper attempts to give the reader a brief overview of the origins of the city of Zawiya, emphasizing the stages of its growth, as the historical study of cities is an indispensable foundation. Many general principles and rules can only be derived from history. Furthermore, it is difficult to understand the contemporary city without studying its historical background. Therefore, the study of the urban network’s structure is only clear through historical analysis. In addition, any attempt to classify cities cannot ignore the historical aspect; however, this study does not delve into the city’s history in the direct sense. Because it is merely a brief overview of the part of its recent past that is an important entry point in determining the period of its emergence and tracing the course of its development - most of the ancient civilizations that flourished on the shores of the Mediterranean Sea left traces of themselves in Libya at different periods of time and built small cities, and others large ones, on the Libyan shores. The city of Zawiya is one example of this. The Phoenicians built trading centers on the Libyan coast, and these centers then turned into important cities that rivaled the urban centers of other powers in the Mediterranean basin.